Measuring the Information Literacy Skills of Secondary School Students of Bhimber, Azad Jammu and Kashmir (AJK) - Waqas, Muhammad; Choudhary, Farkhunda Rasheed (UMT Education Review, 2021)
Information literacy is defined as a set of skills required to find, retrieve, analyze, and use information. Due to the knowledge explosion and the availability of a vast amount ofinformation resources, this era is known as the “information era”. In the21stcentury, mere replication of knowledge is not enough rather the survival of the personnel is contingent with the practice specific information literacy skills Information literacy skills empower individuals by allowing them to develop their critical thinking skills, enabling them to become independent lifelong learners. This study was conducted to measurethe information literacy skills of secondary school students. The sample comprised 125 secondary school students of Bhimber, Azad Jammu and Kashmir (AJK). An online test was used to measure the level of information literacy of students. The test comprised 32 items. The time limit of the test was 60 minutes. The data was analyzed using descriptive statistics. It is important to mention that out of 125 students, only 5 students attained a high score ranging between 80.6 and 90.5.These students finished their test within 41-50 minutes. Whereas the rest of the students scored less than 50%. It was concluded that the selected secondary school students could not use technology in their day-to-day activities. It is recommended that students should beprovided with opportunities to use technology in their day-to-day life at school level. Moreover, it is suggested here that a comprehensive course on information literacy skills andtheir practical applications should be mandatory at secondary level. Keywords: critical thinking skills, information literacy skills, lifelong learning